Detection of Extended-Spectrum β-Lactamases Producing Escherichia Coli from Beef in Mansoura, Egypt - Al-Shawa, Mohammed; Sadat , Asmaa; Awad, Amal (Journal of Advanced Veterinary Research, 2023)
The objective of the current study was to identify extended-spectrum β-lactamase-producing Escherichia coli (ESBLs) from beef meat in Mansoura City, Egypt.Randomly selected 150 buffalo meat samples were obtained from retail butcher shops located in Mansoura City, Egypt. Samples were inoculated into enriched broth media and then directly streaked on E. coli selective agar for selective isolation of E. coli. A biochemical examination was performed for the preliminary identification of E. coli. Suspected E. coli isolates were then confirmed by PCR targeting 16S rRNA. Confirmed E. coli isolates were tested for their susceptibility to antimicrobials by using Kirby–Bauer disc diffusion method. Additionally. E. coli were tested for the presence of β-lactamases (blaCTX, and blaSHV and blaTEM) using PCR. E. coli was isolated from 37 out of 150 tested samples with a total prevalence of 24.66 %. E. coli isolates revealed a high resistant against cefotaxime and ceftazidime, and moderate resistance against amoxyclavulanic acid, while a high sensitivity of E. coli was displayed against meropenem and imipenem. Moreover, the tested E. coli (n=37) harbored ESBLs genes with percentages of 40.5% for both blaCTX, and blaSHV and 35% for blaTEM. E. coli produces extended-spectrum β -lactams that were isolated from meat and contained a substantial level of antibiotic resistance genes. To increase food processing quality and provide safe food for consumers, it is crucial to build food traceability and monitoring systems for meat and meat products.